The Rcs System in Enterobacteriaceae: Envelope Stress Responses and Virulence Regulation - Meng, Jiao; Young, Glenn; Chen, Jingyu (Frontiers in Microbiology, 2021)
The bacterial cell envelope is a protective barrier at the frontline of bacterial interaction with the environment, and its integrity is regulated by various stress response systems. The Rcs (regulator of capsule synthesis) system, a non-orthodox two-component regulatory system found in many members of the Enterobacteriaceae family, is one of the envelope stress response pathways. The Rcs system can sense envelope damage or defects and regulate the transcriptome to counteract stress, which is particularly important for the survival and virulence of pathogenic bacteria. In this review, we summarize the roles of the Rcs system in envelope stress responses and virulence regulation. We discuss the environmental and intrinsic sources of envelope stress that cause activation of the Rcs system with an emphasis on the role of RcsF in detection of envelope stress and signal transduction. Finally, the different regulation mechanisms governing the Rcs system’s control of virulence in several common pathogens are introduced. This review highlights the important role of the Rcs system in the environmental adaptation of bacteria and provides a theoretical basis for the development of new strategies for control, prevention, and treatment of bacterial infections.